(untitled) (Journal of Asian Development Studies, 2026)
The ready-made garments (RMG) sector of Bangladesh has got a greater facet than any other sector in terms of growth and foreign exchange earnings. It makes a significant contribution to the national economy by creating generous employment opportunities and reducing poverty through socioeconomic development. Despite unquestionable success story, this sector has got a number of formidable challenges for the future growth. The present study has made a search on different dimensions of contribution and challenges of RMG industry in Bangladesh. To accomplish the task, a descriptive research based on study of available records is conducted. The study reveals that since its inception, especially during the last three decades, the RMG industry contributed significantly through creation of physical infrastructure which is demonstrated by 4222 RMG units along with the development of human capital as around 4 million workforce are directly involved in this industry. It has also contributed tremendously through empowering women as almost 90 percent of its labor force is female which ranked the highest in South-East Asia. In terms of core economic consideration RMG holds almost 14.07 percent of the GDP of Bangladesh as well as the 81 percent of the total export earnings. The study however, identifies some challenges towards its future development including unskilled workers, improper infrastructure, energy crisis, bank loan and high rate of interest, high tax rate, intricate social compliance, political crisis, lack of market and product diversification, compliance pressure of accord and alliance and lack of integration. Therefore, collaborative and coordinated steps from both public and private sectors need to be initiated to overcome these challenges